A halophilic Chromohalobacter species from estuarine coastal waters as a detoxifier of manganese, as well as a novel bio-catalyst for synthesis of n-butyl acetate - Pereira, Flory; Kerkar, Savita; Dias, Dominic Savio; Gobre, Vivekanand V. (Frontiers in Microbiology, 2023)
Chromohalobacter spp. are moderately halophilic bacteria belonging to the family Halomonadaceae. A manganese (Mn) tolerant, moderately halophilic Chromohalobacter sp. isolated from the sediments of a solar saltern, influenced by the influx of ferro manganese ore transported through the Mandovi estuary in Goa, India was explored for its ability to tolerate and immobilize Mn in amended and unamended media with 20% natural salt concentration (w/v). In aqueous media supplemented with 0.1mM Mn, the Chromohalobacter sp. was capable of sequestering upto 76% Mn with an average immobilization rate of 8 mg Mn /g /day. Growth rate kinetic analysis using Gompertz mathematical functions was found to model the experimental data well. The model inferred that the maximum growth rate of Chromohalobacter sp. was at 10% natural salt concentration (w/v). The Chromohalobacter sp. was further found to be multimetal tolerant showing high tolerance to Iron (Fe), Nickel (Ni) and Cobalt (Co), (each at 4 mM) and tolerated Manganese (Mn) upto 6 mM. Morphologically, the Chromohalobacter sp. was a non spore forming, Gram negative motile rod (0.726µ x 1.33µ). The adaptative mechanism of Chromohalobacter sp. to elevated Mn concentrations (1 mM) resulted in the reduction of its cell size to 0.339µ x 0.997µ and the synthesis of an extracellular slime, immobilizing Mn from the liquid phase forming Manganese oxide, as confirmed by Scanning Electron Microscopy. The expression of Mnx genes for manganese oxidation futher substantiated the finding. This bacterial synthesized manganese oxide also displayed catalytic activity (~50% conversion) for the esterification of butan-1-ol with CH3COOH to yield n-butyl acetate. This Chromohalobacter sp. being indigenous to marine salterns, has adapted to high concentrations of heavy metals,and high salinities can withstand this extremely stressed environment and thus holds a tremendous potential as an environmentally friendly “green-bioremediator” of Mn from euryhaline environments. The study also adds to the limited knowledge about metal-microbe interactions in extreme environments. Further, since Chromohalobacter sp. exhibits an excellent catalytic activity for the synthesis of n-butyl acetate, it would have several potential industrial applications.